ANALISIS KARAKTER PENDUKUNG HASIL DAN HASIL MUTAN (M4) PADI (Oryza sativa L.) INPAGO UNRAM I DAN BAAS SELEM - Ap, Julizar Auladia; Suliartini, Ni Wayan Sri (Fakultas Pertanian Universitas Mataram, 2025)
Efforts to improve the quality of rice varieties are carried out by genetic mutations to bring about changes in plants can produce varied plant characteristics. This study aims to find out whether there is a significant difference in the appearance of the supporting characters of results and yields and to determine the superior mutant genotype (M4) of Inpago Unram I, Baas Selem, and Inpari 32 rice. This research was carried out from March to August 2023 in Saribaye Village, Lingsar District, West Lombok Regency, NTB. The design used is the Group Random Design (RAK) which consists of 21 treatments, namely 10 rice mutants Inpago Unram I, 10 rice mutants Baas Selem, and Inpari-32. The observation data was analyzed using diversity analysis at a real level of 5%. The significantly different variables were further tested using orthogonal contrast analysis. The results of the diversity analysis showed that there were real different characteristics, namely plant height and the number of empty grains per panicle. Inpago Unram had a high yield with a grain weight of 40.55 grams per clump, Baas Selem had a grain weight of 34.77 grams per clump, Inpari-32 had the lowest yield of 32.64 grams.